Revitalizing a village for mental health in watershed area in Central Kalimantan, Indonesia - Missesa, Missesa (GHMJ (Global Health Management Journal), 2022)
Most of the inhabitants in Central Kalimantan live in a residential area which is located close to the watershed (DAS). The geography of the watershed is a challenge for affordable health services, particularly in mental health services. Patients with mental disorders who do not get health care services will have a high risk of experiencing recurrence due to withdrawal of medication. There are needs to be solved by various parties to overcome this problem. Mental healthcare delivery in this area is more likely to be effective and sustainable if supported by the secondary level of care in particular the local Health Department. This photo essay pictures our effort to revitalize a village for mental health in watershed area in Central Kalimantan, Indonesia. The concept of "Desa Siaga Sehat Jiwa” (Healthy Village) focuses on empowering communities and local health authorities to work together to improve mental health. A community-based mental health initiative has been conducted in cooperation with mental health nurses raising awareness of mental health. Nurse educators at the Health Polytechnic Palangka Raya have an important role to play in raising awareness of mental health in village communities. We delivered and facilitated a discussion session to revitalize the village in order to increase their awareness to mental health. For the collaboration, to the meeting, we invite the village local stakeholders including the community leaders, health providers from the Primary Health Care, soldiers, police, and community representatives. To sustainably continue the forming of "Desa Siaga Sehat Jiwa”, a mutual agreement was signed by the stakeholders as a commitment to work together to create a healthy community in improving mental health in the villages.